UNDERGROUND STRUCTURE RIGHTS IN RUSSIA: ACTUAL PROBLEMS - Allanina , Lilija M. (International Journal of Psychosocial Rehabilitation, 2020)
The topicality of this paper is predetermined by the public interest in the theme of the underground structure rights in Russia. The article deals with the specifics of subsurface structures as objects of law, actual problems of Cadastral Registry and State registration of real property rights for the mentioned facilities are analyzed. The purpose of the article is to consider the impact of various factors on the underground structure rights including the state-legal regulation of relations. Methods include case study, comparison, legal norm interpretation, methods of formal logic and others. The novelty of the research can be seen in clarifying the problem of the absence of a legal definition of a subsurface structure, also in a new view of the relationship between a land plot, a subsurface site and things either in the form of subsurface structures or an entire complex that forms a complex thing. In this case, the subsurface plot will not enter as an integral part of a complex thing, and it will not cease its legal existence accordingly. The peculiarity of the right to use subsoil for the purposes of construction and maintenance of subsurface structures is not only in a stable and termless nature of use but also in the strong connection between the rights to the subsurface parcel, surface plot and subsurface structures. The underground sites and underground structures should be identified as three-dimensional objects of law. At the moment, such conditions in Russia have not been created yet. The paper concludes that it is necessary to begin preparation of an integrated amendment package to improve the mining and civil legislation, including the Law dated February 21, 1992 No. 2395-1 "On Subsoil" modified by the Law of August 3, 2018 No. 342-FZ with regard to the legal mechanisms for registration the ownership for subsurface facilities. In the cadastral information system, conditions for three-dimensional registration of facilities should be created.